Prevalence and predictors of burnout among nurses during COVID-19: a cross-sectional study in hospitals in central Uganda - Amir Kabunga; Ponsiano Okalo (BMJ Open, 2021)
Objective To determine the prevalence of burnout and associated factors among nurses during COVID-19 in central Uganda.Design A cross-sectional design.Setting Nurse from one referral and four general hospitals. These were reception centres and cared for patients with COVID-19 in central Uganda.Participants 395 nurses.Main outcome measures Burnout scores.Results Of the total 395 participants, 65.1% (n=257) were female; 40% (n=158) had a diploma; 47.1% (n=186) were single; and 39.2% (n=155) had worked for 11–15 years. The results show that 40% (n=158), 41.77% (n=165) and 18.23% (n=77) reported high, average and low levels of burnout, respectively. The results show that the predictors of nurses’ burnout were personal protective equipment (PPE) (OR: 7.1, 95% CI 4.08 to 12.31) and increased workload (OR 4.3, 95% CI 2.43 to 7.93).Conclusion This study of nurses working in hospitals dealing with patients with COVID-19 in central Uganda reported high rates of burnout, and it was associated with PPE and workload. Interventions like contracting new nurses to reduce workload, the WHO guidelines on PPE, adjusting working hours and ensuring hours of effective rest should be adapted.